Penerapan Metode NBM, REBA, dan QEC untuk menurunkan Risiko Kerja di PT XYZ - Worldailmi, Elanjati; Ulinuha, Tamara Hanum; Hertanta, Bayu (Faculty of Industrial Technology Universitas Islam Indonesia, 2025)
The high number of defects in the ironing process at PT XYZ indicates potential ergonomic problems that impact product quality and worker health. This study aims to assess ergonomic risk levels and identify the main causes of musculoskeletal complaints among ironing operators. The Nordic Body Map (NBM) method was used to measure musculoskeletal complaints, the Rapid Entire Body Assessment (REBA) to assess work posture in detail, and the Quick Exposure Check (QEC) to evaluate ergonomic risk factors comprehensively. The study was conducted on four ironing operators, with primary posture measurements taken from the operator with the most representative posture pattern. The NBM results showed that the majority of workers were in the moderate risk category with dominant complaints in the forearms and wrists. The REBA analysis produced a score of 7, indicating action level 2 and requiring improvement in work posture. Meanwhile, the QEC results showed a very high risk (exposure score ≥ 70%) in all operators, especially in the wrist and shoulder segments. Based on these findings, root causes were identified and grouped into machine, method, human, and environment aspects using a fishbone diagram. Recommendations for improvement include anthropometrically based workbench redesign, adjustments to production targets, improved work methods, and environmental controls. This research provides a basis for ergonomic improvements to reduce the risk of injury and improve the quality of the ironing process at PT XYZ.